Enhanced Multiple Pulse Position Modulation Aided Reverse Polarity Optical OFDM System With Extended Dimming Control - Zixian Yang; Ming Jiang; Lin Zhang; Hong-Zhou Tan (IEEE Photonics Journal)
In this paper, we propose a multiple pulse position modulation (MPPM) aided reverse polarity optical orthogonal frequency division multiplexing scheme that aims to enhance the spectral efficiency (SE) for dimmable visible light communication (VLC) systems. In this scheme, we exploit the MPPM patterns to transmit the extra information bits without the increase of the signal bandwidth and, thus, improving the SE. Specifically, for each frame, the binary information stream is divided into two parallel groups, where the first group is used to select the patterns of MPPM symbols, while the other is modulated by optical OFDM. Then, the time-domain OFDM signal is accommodated by both the “on” and “off” slots of MPPM symbols for transmissions over the VLC channel. With the aid of a forward error correction aided decision feedback approach, the system performance can be further improved. Theoretical analyses on the dimming level, the average power consumption and the frame error probability are provided and verified by simulation results. It is shown that the proposed system with extended dimming control can achieve the highest effective spectral efficiency in most scenarios without substantially increasing the computational complexity, while still maintaining a power consumption level similar to those of the reference systems.